Design and implementation of a PSOC-based modular electronic expansion card for the development of applications of embedded systems - Alvarado Fernández, Alberto (2019)
The city of Tacna is no stranger to the exposure of pollutants such as sedimentable particles that are generated due to stable weather conditions, urban growth, increased vehicular traffic, urban expansion, unpaved streets, among other factors. . Through the present research work that was carried out in the city of Tacna, it was possible to determine the concentration of sedimentable atmospheric dust in our city, for which 08 sampling stations were established where the Passive Sampling methodology was applied, which consisted of the placement of glass plates located on the upper level of homes and / or institutions, for a period of 04 months and at that time the information was collected every 30 calendar days. For the location of the stations to be sampled, the type of road, population density and traffic were taken into account; managing to determine with it 08 sampling zones located in the Center and Intermediate zone of the city of Tacna, taking as reference the civic walk of the city. The results obtained from the sampling of sedimentable particles indicate a final average value of 1.07 mg / cm2 / month in all sampling stations, which is in the order of 0.57 mg / cm2 / month above the guide values for atmospheric particles sediments of the World Health Organization - WHO, set at 0.50 mg / cm2 / month. According to the results obtained, it was possible to determine 3 points with a greater degree of significance, in which the PM2.5 and PM10 were monitored with the mobile station where the Automatic Monitoring methodology was applied.